ANALISIS KOHESI DAN KOHORENSI WACANA BERITA MAHASISWA ITS JADI JAWARA DI RUMANIA DALAM DETIKNEWS - Khoifatu Amalia Shofiani, Arisni; Puspa Wiyanti, Belia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
This journal aims to explain the results of cohesion and cohesion analysis in the ITS Student news discourse to be the Champion in Romania on the May 14, 2019 edition of Deiknews. This study uses descriptive methods describing the results of the analysis found in this study. This research is a type of qualitative research because the results of the research are descriptive and tend to be analysis. The techniques used for data collection are the techniques of listening and note taking techniques. The results of this study are (1) the use of cohesion, (2) the use of cohesion. Cohesion is the integration between the parts that are characterized by the use of language elements. Cohesion is divided into two parts, lexical cohesion and grammatical cohesion. Grammatical cohesion includes conjunction, reference, release, substitution. Lexical cohesion includes antonyms, synonyms, repetitions, metonymy, and hypomini. Whereas, cohorence is the relationship between elements that are one with the other elements so that it has an integrated meaning. The most common combination in discourse is cohesion, namely grammatical cohesion. Grammatical cohesion is reference and conjunction. Therefore, the news discourse does not pay attention in terms of language and only prioritizes the actuality of the content of the news.